THE LANGUAGE OF THE EXILED DURING THE INDEPENDENCE WAR - Gómez Baeza, Nicolás; Retamal Navarro, Felipe; Rivas Rodríeguez, Javier (Revista de Historia Social y de las Mentalidades, 2011)
After exposing briefly the main theoretical framework of the political thinking and metaphorology, the article analyses the main features of the language used by the exiled -under the charge of being a menace to the independentist movement - in the letters directed to the political authorities of the newborn republic twice during the uprising emancipatory - in the year 1813, during the ruling of José Miguel Carrera, and between 1817 and 1818, during the ruling of Bernardo O`Higgins. Afterwards, it is concluded that along the process there was an important transformation of the discursive repertoire used by the exiled, from a predominance of sensitive body experience as a talk resource field to a predominance of the resources linked to legality and the praising of the Americanist cause.